Além da atividade proteolítica das metaloproteases: atividade imunomoduladora da Thimet oligopeptidase (TOP) no tratamento do melanoma murino B16F10Nex2 - De Amat Herbozo, Carolina Cecilia [UNIFESP] (2017)
Previous studies in our laboratory have shown that two bacterial metalloproteases, oligopeptidase A (OpdA) and arazyme, have antitumor activity. This property was independent of their proteolytic activity, and it was mediated by an immunomodulatory effect, involving the activation of antigen presenting cells (APCs). Those results could indicate that OpdA and arazyme were recognized by APCs because of their bacterial origin or otherwise, the immunomodulatory ability was a characteristic of metalloproteases in general, regardless of their origin. The aim of the present study was to evaluate the immunomodulatory and antitumor activity of thimet oligopeptidase (TOP), a murine metallopeptidase, in the B16F10-Nex2 murine melanoma model. Expression and purification of the recombinant version of TOP (rTOP) were optimized, and active and heat-inactivated forms were analyzed. rTOP did not show direct cytotoxic activity in vitro on tumor cells. In vivo assays showed that rTOP has a dose-dependent antitumor activity only in the metastatic, but not in the subcutaneous model. The antitumor effect was independent of the rTOP proteolytic activity, and dependent on a functional adaptive immune response, since it was abolished in immunodeficient animals. Cytokine analysis of serum samples and ex vivo restimulated spleen and lymph node cells revealed that a tumor-specific Th1 response was favored in rTOP treated animals. The active form of the metalloprotease stimulated an increase of IFN-γ, whereas the heat-inactivated form inhibited IL-10 production. Murine bone marrow-derived macrophages and dendritic cells (BMDMs and BMDCs, respectively), were activated in the presence of both active and inactive rTOP, resulting in increased NO production, IL-12p40, TNF-α and IL-10 secretion, and expression of the costimulatory molecules CD80, CD86 and CD40 in BMDCs. Assays in the presence of polymyxin B and with proteinase K-degraded metaloprotease demonstrated that the immunomodulatory activity of rTOP on APCs is not due to the residual LPS of the recombinant preparation. Assays with cells obtained from knockout mice or using specific antagonists/inhibitors determined that the activation of BMDCs is dependent on the presence and function of the TLR4 receptor and the MyD88 and TRIF adapters, and participation of the JNK, p38 and MAP/ERK kinases. In addition, the MyD88 pathway was essential for the antitumor effect of rTOP in the metastatic melanoma model in vivo. In conclusion, rTOP exhibits antitumor activity in the murine metastatic melanoma model mediated by an immunomodulatory effect, and the activation of APCs by rTOP requires the same receptor and signaling pathways as the bacterial metalloproteases studied before.